2013
DOI: 10.3390/plants2010107
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Composition, Biosynthesis and Remodeling during Pollen Tube Growth

Abstract: The pollen tube is a fast tip-growing cell carrying the two sperm cells to the ovule allowing the double fertilization process and seed setting. To succeed in this process, the spatial and temporal controls of pollen tube growth within the female organ are critical. It requires a massive cell wall deposition to promote fast pollen tube elongation and a tight control of the cell wall remodeling to modify the mechanical properties. In addition, during its journey, the pollen tube interacts with the pistil, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 230 publications
(338 reference statements)
2
118
0
1
Order By: Relevance
“…In addition, in Brassica campestris, alteration of the expression of B. campestris MALE FERTILITY2 (coding for a putative PGase) resulted in an overdeveloped intine and abnormal germination (Huang et al, 2009). The transcriptome analysis of Arabidopsis pollen grains has revealed that six genes coding for putative PGases and four genes encoding putative PLs are strongly expressed in dry pollen grains and pollen tubes (for review, see Mollet et al, 2013). Taken together, these observations suggest that the early action of PME48 during maturation of the pollen grain also may be required to ensure the future degradation of the intine by PGases and PLs (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, in Brassica campestris, alteration of the expression of B. campestris MALE FERTILITY2 (coding for a putative PGase) resulted in an overdeveloped intine and abnormal germination (Huang et al, 2009). The transcriptome analysis of Arabidopsis pollen grains has revealed that six genes coding for putative PGases and four genes encoding putative PLs are strongly expressed in dry pollen grains and pollen tubes (for review, see Mollet et al, 2013). Taken together, these observations suggest that the early action of PME48 during maturation of the pollen grain also may be required to ensure the future degradation of the intine by PGases and PLs (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…This labeling pattern is also observed in pollen tubes from plants possessing a solid style, such as species in the Solanaceae (potato [Solanum tuberosum], tobacco, and petunia [Petunia hybrida]), the Oleaceae (jasmine [Jasmium spp. ]), and the Poaceae (maize [Zea mays]; Li et al, 1994;Qin et al, 2007; for review, see Mollet et al, 2013), and those with a hollow style, such as lily (Jauh and Lord, 1996). The methylesterified HG in the apical dome of the pollen tube is thought to provide sufficient plasticity of the cell wall to sustain pollen tube growth (Chebli and Geitmann, 2007).…”
mentioning
confidence: 99%
“…Pollen allergens are known to cause allergic reactions in humans and are therefore studied intensively. Although their biological function in plants is not fully elucidated yet (Jiménez-López et al, 2011), it is suggested that these proteins may weaken the cell wall of the maternal tissue to ease the penetration of the pollen tube into the stigma (Cosgrove et al, 1997;Mollet et al, 2013). In tomato, competition experiments have been performed between wild-type pollen and pollen in which one of these pollen allergens has been mutated.…”
Section: Homology Of Heat Stress Responses Between Speciesmentioning
confidence: 99%
“…The cell wall is more expandable in the hemispherical tip and more rigid in the cylinder, and tip-targeted exocytosis of new cell wall materials and membranes increases the expandability of the tip surface. The internal machinery that supports pollen tube growth is the dynamic actin cytoskeleton, which is composed of thick, long F-actin bundles aligned to the long axis in the cylinder tube, and a fine, short F-actin-formed fringe located in the subapical region (i.e., the hemispherical tip region excluding the extreme apical part), which rapidly turns over and keeps pace with growth Mollet et al, 2013). F-actin bundles serve as "tracks" for transporting subcellular organelles and also participate in cytoplasmic streaming.…”
Section: Introductionmentioning
confidence: 99%